SURVEY OF COMMUNITY ADAPTATION IN NEW NORMAL DURING THE COVID-19 PANDEMIC IN NAKHON NAYOK - Samart, Phanupong (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The purposes of this research were to study: 1) The people’s behavior, adaptation, and learning towards the New Normal lifestyle during the Covid-19 pandemic on the aspects of the economy, health, society and environment, IT usage, and education. 2) People’s anxiety during the Covid-19 pandemic 3) Develop the knowledge-creation model for people’s adaptation to the New Normal lifestyle, and 4) Present the preventive and integrated measures among Rajabhat Universities and involved local agencies. This research was survey research and by mixed methods, both quantitative and qualitative. For the quantitative data, the sample consisted of 400 samples, selected by a simple random sampling method. The data were collected through questionnaires and assessment forms and was analyzed by a computer software program. Percentage and frequency were used to describe the data. For the qualitative data, 21 key informants were selected and collected through in-depth interviews. The data were analyzed by using content analysis. The results of this study found that: 1) People’s behavior, adaptation, and learning during the Covid-19 pandemic were impacted on the economy, health, society and environment, IT usage, and education. 2) People’s anxiety during the Covid-19 pandemic was found in five aspects: the economy, health, society and environment, IT usage, and education. People have developed continuous anxiety and tiredness from caring for their family members. 3) For the development of learning behavior over the New Normal, was found in six aspects: the economy, mental and physical health, society and environment, continuous following of the news, usage of communicative devices, students’ education and innovation. 4) The guidelines for preventive and integrated measures among Rajabhat Universities and involved agencies in Nakhon Nayok were emphasized for future planning, strengthening communities, and the call for the government to assist with occupational training for the local people.